Nanostructured Membranes for Water Purification - Omowunmi, A. Sadik; Du, Nian; Yazgan, Idris; Okello, Veronica (My University, 2014)
Nanoscale materials can be used to achieve wastewater purification, desalination, and inactivation of pathogenic bacteria and viruses, as well as for the adsorption and/or degradation of contaminants [1 16]. The development and sustainability of water treatment technologies have been mostly driven by three primary factors: the discovery of new rare contaminants, the promulgation of new water quality standards, and cost [17 23]. Most sources of water used for public drinking water supplies are not of suitable quality for consumption without some form of treatment
Keywords: Nanostructured Membranes; Water Purification